Effect of COVID-19 on Women Entrepreneurship in India : A Literature Review - Mahato, Jogeswar; Gaurav, Kumar (AMC Indian Journal of Entrepreneurship, 2023)
Women enterprises lack the resources to combat potential hazards and are unable to deal with the expenses of an infinite slowdown in operations. Inadequate funds and liquidity impede the ability of women owned businesses to compensate their employees and make use of technology. The present study aims to examine the social and economic effects of COVID-19 on women owned businesses across the nation. The data retrieval technique incorporates an exploratory investigation with a systematic evaluation of multiple journal databases. A comprehensive qualitative and quantitative analysis of peer-reviewed journals from around the globe was conducted to identify, attribute, and investigate concerned idea of the study.